Interdisciplinary approach in structuring the content of the humanities (Pedagogy of Higher and Secondary Education, 2016)
Ustinova V. A. Interdisciplinary approach in structuring the content of the humanities.Article is devoted to studying the particular qualities of an interdisciplinary approach in the process of structuring the content of the humanities. Scientific methods were used to achieve this goal. They are analysis and comparison of pedagogical sources for the research problem; compilation and synthesis of scientific knowledge concerning the characteristics of the implementation of an interdisciplinary approach. In this article, the main ways of interdisciplinary inplementation in the professional training of students of pedagogical universities were defined.The urgency of the problem is caused by political and social changes that provide young people the opportunity to free self-realization in different countries, the objective necessity of formation of ideological understanding and holistic perception of the scientific and cultural development of mankind. The formation means of such a worldview is aninterdisciplinary approach in education.The aim of the article is to reveal the role of the interdisciplinary approach in the process of humanization and humanitarization of education.Research objectives are defined according to the purpose: to analyze the basic methodological approaches to the process of structuring the content of the humanities; to characterize interdisciplinary communication as an important pedagogical condition of formation the structuring process of the content of the humanities.Interdisciplinary in education is one of the main directions of the organization of educational process in higher pedagogical school as it is based on the interdisciplinary nature of current knowledge.
Keywords: Interdisciplinary approach; multidisciplinary; interdisciplinary contents; liberal education; the humanities; humane education; structuring